2015
DOI: 10.1177/000313481508101009
|View full text |Cite
|
Sign up to set email alerts
|

Revising Recommendations and Outcome Measurements after Complex Open Abdominal Wall Reconstruction

Abstract: Grading systems developed by the Ventral Hernia Working Group (VHWG) for complex open abdominal wall reconstruction rely on limited outcomes: surgical site occurrence (SSO) and hernia recurrence. This does not account for the longitudinal restoration of a functional abdominal wall and the ability to correct complications. We performed a single-site, retrospective review of consecutive complex open abdominal wall reconstruction interventions with 24-month minimum follow-up to establish reoperation rates and com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 9 publications
0
8
0
1
Order By: Relevance
“…Sixty-five articles described LOD in the context of ventral hernia patients, 9 articles described LOD caused by giant inguinal hernia, and 3 articles described giant diaphragmatic hernia. Sixty-seven articles were from the primary literature, comprising 44 case series, 17 case reports, 4 retrospective database analyses [ 18 , 33 35 ], and 2 retrospective interventional studies [ 36 ] [ 30 ]. Ten articles were from the secondary literature comprising seven editorials, two systematic reviews [ 20 , 37 ] and one consensus questionnaire [ 11 ].…”
Section: Resultsmentioning
confidence: 99%
“…Sixty-five articles described LOD in the context of ventral hernia patients, 9 articles described LOD caused by giant inguinal hernia, and 3 articles described giant diaphragmatic hernia. Sixty-seven articles were from the primary literature, comprising 44 case series, 17 case reports, 4 retrospective database analyses [ 18 , 33 35 ], and 2 retrospective interventional studies [ 36 ] [ 30 ]. Ten articles were from the secondary literature comprising seven editorials, two systematic reviews [ 20 , 37 ] and one consensus questionnaire [ 11 ].…”
Section: Resultsmentioning
confidence: 99%
“…Wounds classified as CDC class I (clean) may be classified as VHWG 2012 grade 1 (clean cases; no comorbidity) or 2 (clean cases + comorbidity, history of infection), while CDC clean-contaminated, contaminated, and infected wounds would be VHWG 2012 grade 3. 12 The VHWG 2010 classification suggests the use of synthetic mesh for low-risk defects (grade 1) and biological mesh for higher-risk defects (grade 2) and contaminated or infected wounds (grades 3 and 4). However, given the significantly higher acquisition cost of biological meshes compared to synthetic ones, often there is a shift toward choosing synthetic mesh even in case of wound contamination.…”
Section: Literature Review and Clinical Data Synthesismentioning
confidence: 99%
“…It has been suggested that combining these grades and stratifying contamination according to the Centers for Disease Control classification of wound contamination scale improves the accuracy of prediction of wound morbidity . However, others have supported the use of separate grades in cases of severe contamination .…”
Section: Introductionmentioning
confidence: 99%
“…The advent of biological mesh was hoped to provide the solution to this, and early results demonstrated satisfactory outcomes in contaminated settings . Some issues have arisen around the use of crosslinked meshes and the risk of fistula recurrence and the lack of data on long‐term outcomes . The variety of products available and a lack of randomized trials add to the confusion.…”
Section: Introductionmentioning
confidence: 99%